The Farmer, the Blue-collar, and the Monk: Understanding Economic Development through Saturations of Demands and Non-Homothetic Productivity Gains - Elie Gray; André Grimaud; David Le Bris (Center for Economic Studies and ifo Institute (CESifo), 2018)
To explain the process of development historically documented, we consider a model with three economic sectors (agriculture, manufacturing and services) characterized by different productivity gains and by saturation levels in the demands of agricultural and manufactured goods. Our parsimonious model captures within a single framework the process of development which is characterized by the structural changes in the workforce across sectors, variable growth rates (an initial “Malthusian regime” exhibiting slow growth, a fast growth regime after a takeoff, and a gradual slow down leading to a possible new stagnation) and the relative evolutions of prices across sectors. Reasonable calibration generates results quantitatively close to the observed empirical facts.
Keywords: O10; O40; N10; 330; growth mode; structural change; unified growth; economic development; saturation of demands